First record of the genus Euchariomyia Bigot, 1888 from China (Diptera: Bombyliidae) - Yao, Gang; Yang, Ding; Evenhuis, Neal L. (Zootaxa, 2009)
The genus Euchariomyia Bigot is a small Oriental genus with three known species. It is recorded from China for the first time with one known species. Male and female genitalia of the species Euchariomyia dives Bigot are described. A key to the genera of Bombyliinae from China is presented.